In search of an elusive Antarctic circumpolar wave in sea ice extents: 1978–1996 - Gloersen, Per; Huang, Norden E. (Polar Research, 1999)
For ease in discerning an Antarctic circumpolar wave in the perimeter of the ice pack, we construct a time series of the sea ice extents (essentially the area within the ice perimeter) in 1-degree longitudinal sectors for the period 1978-1996, as observed with the multichannel microwave imagers on board the NASA Nimbus 7 and the DOD (Dept. of Defense) DMSP (Defense Meteorological Satellite Program) F8, F11, and F13 satellites. After converting the time series into complex numbers by means of a Hilbert transform, we decompose the time series of the 360 sectors into its complex principal components (CPCs), effectively separating the spatial and temporal values. Then we decompose the real and imaginary parts of the temporal portions of the first three CPCs (complex principal compenents) by Empirical Mode Decomposition into their intrinsic modes, each representing a narrow frequency band, resulting in a collection of three CPCs for each intrinsic mode. Finally, we reconstruct the data in two different ways. First, we low-pass filter the data by combining all of the intrinsic modes of each CPC with periods longer than two years, which we designate as lowpass filtered. Next, we select the intrinsic mode of each CPC with periods of approximately four years, which we designate the quasiquadrennial (QQ) modes. The low-pass filtered time series shows eastward propagating azimuthal motion in the Ross and Weddell Seas, but no clearly circumpolar motion. The QQ time series, on the other hand, clearly shows eastward propagating circumpolar waves, but with occasional retrograde motion to the west.
Keywords: Rosshavet; Sørishavet; Weddellhavet; havis; klimatologi; meteorologi; oseanografi

Iron enrichment with hydrocarboxylic acid and photoreduction of iron under UV and PAR: implications for phytoplankton growth in the Antarctic Ocean. Some preliminary results - Öztürk, Murat; Sakshaug, Egil (Report of the Norwegian Antarctic Research Expedition 1997/98, 1999)
Keywords: NARE 1997/98; Sørishavet; fytoplankton; marin biologi; oseanografi

Report of the Norwegian Antarctic Research Expedition 1997/98 - Tveraa, Torkild (ed.); Winther, Jan-Gunnar (ed.) (Norsk Polarinstitutt, 1999)
Publication Title: Meddelelser
Keywords: Antarktis; NARE 1997/98; biologi; geodesi; glasiologi; oseanografi

Research cruise of the Scandinavian South African Antarctic expedition, December 1997 to February 1998 - Froneman, P.W.; Pakhomov, Evgeny; Turner, D.; Abrahamson, K.; Karlsson, B.; Godhe, Anna; Bertilsson, Stefan; Graneli, Wilhelm; Carlsson, Per; Wängberg, Sten-Åke; Wulff, Angela; Croot, Peter; et al. (South African Journal of Science, 1998)
Focuses on the Scandinavian/South African Antarctic expedition conducted between December 4, 1997 to February 6, 1998 which determined the role of Southern Ocean in the global carbon cycle in physical and biological oceanographic studies. Aims of the expedition; Underway sampling conducted; Biological results of the expedition; Conclusions.
Keywords: NARE ekspedisjoner; Sørishavet; fytoplankton; krill; marin biologi; oseanografi

Stability of the Thermohaline Circulation to Noisy Surface Buoyancy Forcing for the Present and a Warm Climate in an Ocean General Circulation Model - Skagseth, Øystein; Mork, Kjell Arne (Journal of Physical Oceanography, 1998)
The stabilities of two different circulation regimes in the North Atlantic, 1) the present thermohaline circulation and 2) a weaker thermohaline circulation, are compared using the Hamburg Large Scale Geostrophic (LSG) ocean circulation model. The latter circulation regime is obtained by restoring the LSG model toward an on average 48C warmer air surface temperature corresponding to a doubled atmospheric content of CO 2 . The stabilities of these stationary states are investigated by imposing various amounts of stochastic noise on the surface freshwater flux. The simulations show more variability on secular timescales for the present than for the warm climate. Since the modeled static stabilities for the two climates are relatively similar, the different rates of variability are probably connected to other mechanisms. In the present climate at high latitudes the two buoyancy fluxes due to heat and freshwater are of similar magnitudes but with opposite signs; thus switches between convective and nonconvective periods at secular timescales are possible. In the warm climate the buoyancy flux due to heat dominates. This compensates the effect of the noisy freshwater forcing and thus reduces the potential for secular oscillations. The stronger coupling between the Atlantic and the Southern Ocean for the present relative to the warm climate could also contribute to this difference. Furthermore, the simulations show that the variability of the Antarctic Circumpolar Current transport for the present climate exceeds that of the warm climate. For increasing stochastic noise the present circulation approaches that of the warm circulation. The authors apply a mixture of heat flux and temperature restoring for the surface boundary condition. Comparison with similar works, which apply a pure restoring for surface temperature, shows that the ocean circulation is much less sensitive to forced stochastic freshwater anomalies with the type of boundary condition used herein. A box model is used to illustrate the effects of the surface temperature parameterizations and the different buoyancy forcing for the present and warm climate.
Place: Boston MA, USA Publisher: American Meteorological Society
Keywords: AABW; Sørishavet; Sørishavsstrømmen; geofysikk; havstrømmer; oseanografi; polarområdene; vannmasser

Water masses in the southern Weddell Sea - Gammelsrød, Tor; Myking, Steinar; Nøst, Anders; Skagseth, Øystein; Østerhus, Svein (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: NARE 1992/93; Sørishavet; Weddellhavet; innlandsis; oseanografi; vannmasser

The Antarctic coastal current - physical oceanographic results from NARE 1996/97 - Nøst, Ole Anders; Lothe, Torleif (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: NARE 1996/97; Sørishavet; oseanografi

Report of the Norwegian Antarctic Research Expedition 1992/93 - Orheim, Olav (ed.) (Norsk Polarinstitutt, 1997)
Publication Title: Meddelelser
Keywords: Antarktis; NARE 1992/93; ekspedisjoner; geofysikk; geologi; glasiologi; marin biologi; marin geologi; ornitologi; oseanografi; topografi

Hot water drilling near Filchner station, Ronne ice shelf - Orheim, Olav; Østerhus, Svein; Melvold, Kjetil; Eiken, Trond; Thomsen, Henrik Højmark; Winther, Jan-Gunnar; Bævre, Halvor (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: Antarktis; NARE 1992/93; glasiologi; havstrømmer; isshelf; oseanografi; vannmasser

Report of the Norwegian Antarctic Research Expedition 1996/97 - Winther, Jan-Gunnar (ed.) (Norsk Polarinstitutt, 1997)
Publication Title: Meddelelser
Keywords: Antarktis; NARE 1996/97; biologi; geodesi; geologi; glasiologi; oseanografi

Modelling the ocean response to secular surface temperature transitions - Mork, K. A.; Skagseth, Øystein (Climate Dynamics, 1996)
The ocean response to surface temperature transients is simulated with the use of the Hamburg large-scale geostrophic (LSG) ocean general circulation model (OGCM). The transition, from the present to a climate corresponding to a doubling of the atmospheric CO2 content, is compared with the reversed transition. For the Atlantic, the time scale for the deep ocean to adjust to the temperature changes was similar for both transitions. In the Pacific, the time scale is shorter for the present to warm transition than for the reverse case, a result of increased production of Antarctic bottom water (AABW) during the warm climate. While the transition from cold to warm climate shows no secular variability, the reversed transition generates considerable variability on time scales of 300–400 years. For the warm climate, oscillations with periods of 45 years are found in the Southern Ocean. Results of principal oscillation pattern (POP) analysis indicate that these oscillations are due to interaction between convection in the Southern Ocean and advected salinity anomalies in the Antarctic Circumpolar Current (ACC) and the Southern Pacific Ocean.
Fulltext: https://www.researchgate.net/publication/225411625_Modelling_the_ocean_response_to_secular_surface_temperature_transitions
Keywords: AABW; Sørishavet; Sørishavsstrømmen; geofysikk; havstrømmer; oseanografi; vannmasser

Modelling of Deep-Sea Gravity Currents Using an Integrated Plume Model - Alendal, Guttorm; Drange, Helge; Haugan, Peter M (The Polar Oceans and Their Role in Shaping the Global Environment, 1994)
An integrated plume model is used to describe large scale gravity currents in the ocean. The model describes competing effects of (negative) buoyancy, friction, entrainment and Cariolis farce, as well as a pressure term due to variable plume thickness, on the flux, speed and flow direction of the plume. Equations for conservation of salt and internal energy (temperature) and a full equation of state far seawater is included in the model. The entrainment of ambient water is parameterized with support in empirical data, and a drag coefficient consistent with the entrainment is introduced. The model is tested against the overflow through the Denmark Strait, the flow down the Weddell Sea continental slope, and the outflow of saline water through the Gibraltar Strait and from the Spencer Gulf, Australia. The farmer gain an extra driving mechanism due to the thermobaric effect, while in the two latter cases the initial density difference is so large that this effect is not essential. Order of magnitude fit with measurements requires drag coefficient between 0.01 and 0.1. Conditions susceptible to meander behaviour and a singularity arising from the pressure dependency on the current thickness variations are briefly discussed.
Keywords: Sørishavet; Weddellhavet; havbunnen; havstrømmer; klimamodeller; oseanografi

A model of ice shelf-ocean interaction with application to the Filchner-Ronne and Ross Ice Shelves - Nøst, Ole Anders; Foldvik, Arne (Journal of Geophysical Research: Oceans, 1994)
A simple analytical model has been developed to study the formation of Ice Shelf Water (ISW). ISW is assumed to flow as a buoyancy-driven layer underneath the ice shelf. A relation between potential temperature and salinity in the ISW layer is calculated from the mass and energy balance. This temperature-salinity relation is shown to depend only on the temperature and the salinity of the source water mass and to be practically independent of entrainment and melt rates. The model results are obtained without making any assumptions about entrainment and melt rates. The model is in good agreement with observations under the Ronne Ice Shelf, and it indicates that ISW in the Filchner Depression is formed from Western Shelf Water (WSW) with salinity higher than 34.75 practical salinity units. Such high-salinity water is only observed in the Ronne Depression in the western part of the continental shelf. This implies a circulation of WSW, under the Filchner-Ronne Ice Shelf, from the Ronne Depression into the Filchner Depression. Similarly, the model shows that the ISW observed under J9 at the Ross Ice Shelf has been formed from Low Salinity Shelf Water (LSSW) from the eastern parts of the Ross Sea continental shelf. LSSW must therefore circulate under the eastern parts of the Ross Ice Shelf.
Keywords: Antarktis; geofysikk; isshelf; kontinentalsokkel; oseanografi

Report of the Norwegian Antarctic Research Expedition 1991/1992 - Østerhus, Svein (ed.) (Norsk Polarinstitutt, 1994)
Publication Title: Meddelelser
Keywords: Antarktis; NARE 1991/92; fugler; geologi; glasiologi; ornitologi; oseanografi

Oceanographic and glaciologic investigations through Jutulgryta, Fimbulisen in the 1991/92 season - Østerhus, Svein; Orheim, Olav (Report of the Norwegian Antarctic Research Expedition 1991/92, 1994)
Keywords: Dronning Maud Land; NARE 1991/92; glasiologi; oseanografi

Phytoplankton distribution in relation to sea ice, hydrography and nutrients in the northwestern Weddell Sea in early spring 1988 during EPOS - Bianchi, Franco; Boldrin, Alfredo; Cioce, F; Dieckmann, Gerhard Stephan; Kuosa, Harri; Larsson, A M; Nöthig, Eva-Maria; Sehlstedt, P I; Socal, Giorgio; Syvertsen, Erik E (Polar Biology, 1992)
Phytoplankton biomass and distribution of major phytoplankton groups were investigated in relation to sea ice conditions, hydrography and nutrients along three north-south transects in the north western Weddell Sea in early spring 1988 during the EPOS Study (European Polarstern Study), Leg 1. Three different zones along the transects could be distinguished: 1) the Open Water Zone (OWZ) from 58-degrees to 60-degrees-S with high chlorophyll a concentrations up to 3.5-mu-g l-1; 2) the Marginal Ice Zone (MIZ) from 60-degrees to about 62.5-degrees with chlorophyll a concentrations between 0.1 and 0.3-mu-g l-1, and 3) the closed pack-ice zone (CPI) from 62.5-degrees to 63.2-degrees-S with chlorophyll a concentrations below 0.1-mu-g l-1. Nutrient concentrations increased towards the south showing winter values under the closed pack-ice. Centric diatoms such as Thalassiosira gravida and Chaetoceros neglectum forming large colonies dominated the phytoplankton assemblage in terms of biomass in open water together with large, long chain forming, pennate diatoms, whereas small pennate diatoms such as Nitzschia spp., and nanoflagellates prevailed in ice covered areas. Fairly low concentrations of phytoplankton cells were encountered at the southernmost stations and many empty diatom frustules were found in the samples. The enhanced phytoplankton biomass in the Weddell-Scotia-Confluence area is achieved through sea ice melting in the frontal zone of two different water masses, the Weddell and the Scotia Sea surface waters.
Keywords: Sørishavet; Weddellhavet; biomasse; diatomeer; fytoplankton; havis; hydrografi; marin biologi; oseanografi

The role of the microbial loop in Antarctic pelagic ecosystems - Azam, Farooq; Smith, David C; Hollibaugh, James T (Polar Research, 1991)
Keywords: Sørishavet; fytoplankton; oseanografi; økosystemer

Phytoplankton-bacteria relationship in the Antarctic marine ecosystem - Billen, Gilles; Becquevort, Sylvie (Polar Research, 1991)
Keywords: Sørishavet; Weddellhavet; bakterier; biomasse; fytoplankton; marin biologi; oseanografi; økofysiologi; økosystemer

Primary production in polar waters: relation to nutrient availability - Harrison, W G; Cota, G F (Polar Research, 1991)
Keywords: Sørishavet; fytoplankton; oseanografi

Occurrence of polar seabirds at sea in relation to prey concentrations and oceanographic factors - Hunt Jr, George L (Polar Research, 1991)
Keywords: Antarktis; næring; ornitologi; oseanografi; polarområdene; sjøfugler; økosystemer

Factors controlling the development of phytoplankton blooms in the Antarctic Ocean — a mathematical model - Sakshaug, Egil; Slagstad, Dag; Holm-Hansen, Osmund (Marine Chemistry, 1991)
A mathematical model describing the development of phytoplankton blooms as a function of the depth of the wind-mixed layer, spectral distribution of light, passage of atmospheric low-pressure systems, size of the initial phytoplankton stock and loss rates is presented. Model runs represent shade-adapted, large-celled, bloom-forming diatoms. Periodic deep mixing caused by strong winds may severely retard the development of blooms and frequently abort them before macronutrients are completely exhausted. Moderate depths of mixing (40-50 m) in combination with a moderately large total loss rate (about 0.01 3 h-1) can prevent blooms from developing during the brightest time of the year. Complete exhaustion of macronutrients in the upper waters is likely only if the wind-mixed layer is less than 10 m deep, i.e. in very sheltered waters, and also in the marginal ice zone when ice is melting. We do not exclude the possibility of control of phytoplankton biomass by iron in ice-free, deep-sea parts of the Antarctic Ocean, but the implied enhancement of export production through addition of iron might be restricted because of limitation by light, i.e. vertical mixing.
Keywords: Scotiahavet; Sørishavet; fytoplankton; marin biologi; oseanografi

Observations of ice shelf water at the southern Weddel sea shelf break - Foldvik, Arne; Gammelsrød, Tor; Nordlund, Nina; Nytun, Kjell (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: NARE 1989/90; Sørishavet; Weddellhavet; ekspedisjoner; forskning; isshelf; oseanografi

Microbial autotrophic and heterotrophic eucaryotes in Antarctic waters: relationships between biomass and chlorophyll, adenosine triphosphate and particulate organic carbon - Hewes, Christopher D.; Sakshaug, Egil; Reid, Freda M. H.; Holm-Hansen, Osmund (Marine Ecology Progress Series, 1990)
Microscopical examination of near-surface eucaryotic microbial populations in circumcontinental waters of Antarctica indicated that nanoplankton (<20 μm diameter) dominated in regions with low chlorophyll concentrations (< 1 μg l⁻¹). About 30 % of the mean nanoplankton carbon consisted of heterotrophic flagellates. Heterotrophic microplankton carbon (> 20 μm diameter) was generally less significant. The variation in phytoplankton biomass was the result primarily of changes in cell density of pennate diatoms in the East Wind Drift, and of centric diatoms in the Weddell Sea and the Scotia Ridge region. Autotrophic and heterotrophic carbon as determined by microscopical analysis were compared with data for total particulate carbon, chlorophyll a, and adenosine triphosphate. Estimates for the C:chl ratio of autotrophs increased with decreasing concentrations of chlorophyll a, with mean values of 46 in bloom waters and 144 in 'blue water'. A C:ATP ratio for heterotrophic nanoplankton was estimated to be about 100, while that for heterotrophic microplankton may be lower. Algorithms, incorporating concentrations of chlorophyll a and ATP, are described which allow estimates of autotrophic and heterotrophic microbial biomass.
Publisher: Inter-Research Science Center
Keywords: Sørishavet; alger; biomasse; fytoplankton; marin biologi; oseanografi; plankton; zooplankton

Oxygen 18 and helium as tracers of ice shelf water and water/ice interaction in the Weddell Sea - Schlosser, Peter; Bayer, Reinhold; Foldvik, Arne; Gammelsrød, Tor; Rohardt, Gerd; Münnich, Karl Otto (Journal of Geophysical Research: Oceans, 1990)
Oxygen 18 and helium isotope data from stations located in the Filchner Depression, on the continental slope of the southern Weddell Sea, and in the central Weddell Sea are presented and discussed. The 18O and 4He signals imprinted on the water circulating under the Filchner/Ronne Ice Shelf (Ice Shelf Water, or ISW) due to melting of glacial ice at the base of the ice shelf are traced across the sill separating the Filchner Depression from the Weddell Sea. Low δ18O values are correlated with high 4He concentrations in the ISW found in the Filchner Depression (minimum δ18O values: −0.8‰; maximum 4He concentrations: about 4.7×10−8 cm3 STP g−1). The fraction of glacial meltwater contained in the ISW found in the Filchner Depression is estimated to about 6 to 7‰. The 18O and helium isotope data from the overflowing shelf water component observed on the continental slope confirm the hypothesis that ISW contributes significantly to the Weddell Sea Bottom Water (WSBW). On the basis of a inultiparameter water mass analysis it is discussed which fraction of the WSBW originates from ISW and which other shelf waters potentially could contribute to WSBW.
Keywords: Sørishavet; Weddellhavet; brehylle; geofysikk; hydrografi; isbrem; isshelf; oseanografi; smeltevann; vannmasser

Phytoplankton blooms in the vicinity of palmer station, Antarctica - Holm-Hansen, Osmund; Mitchell, Brian Gregory; Hewes, Christopher D; Karl, David Michael (Polar Biology, 1989)
Fifteen oceanographic stations were occupied in the vicinity of Anvers Island, Antarctica, in January of 1985 and 1987. All stations showed high phytoplankton biomass (4.0 to 30 μg chl-a/liter) which was either uniformly distributed in the upper mixed layer or showed a pronounced sub-surface maximum at 4–5 m depth. As phosphate was less than 0.02 μm and nitrate about 2.0 μm in surface waters, it appears that nutrient limitation of phytoplankton growth may be of importance during such blooms. This view is supported by chemical measurements of the particulate material which showed high chl-a/ATP ratios (about 7.7), as well as high POC/ATP ratios (about 700). Microscopical analysis revealed a dominance of large-celled diatoms and the near absence of heterotrophic protozoans. Size fractionation studies showed that the nanoplankton accounted for only 28% of the total phytoplankton biomass. When phytoplankton biomass reaches the levels found at these stations, it appears that the cells are light-limited and hence dark-adapted, which results in the high chl-a/ATP ratios and the low assimilation values (0.49–1.64) obtained in our studies. Under such conditions greater than 50% of the total phytoplankton biomass is found below the 1% light level.
Keywords: Sørishavet; biomasse; fytoplankton; oseanografi

Icebergs rework shelf sediments to 500 m off Antarctica - Barnes, Peter W.; Lien, Reidar (Geology, 1988)
Icebergs and sea ice rework the sediments of high-latitude shelves, producing modern diamicts (ice-keel turbates) unrelated to glacial proximity. Off Antarctica, sidescan sonar data indicate the presence of ice-gouge features formed by the physical interaction between ice keels and the sea bed. These are recognized as incisions a few metres deep and tens of metres wide, in water depths up to 500 m. On the submarine bank tops and slopes off Wilkes Land and in the Weddell Sea, subcircular depressions 30 to 150 m in diameter, a washboard pattern, and hummocky bed features also represent iceberg-resting sites. The freshness of sea-bed morphology, nearby Holocene sediment ponding, and active hydraulic sedimentary processes indicate that the sea floor is being reworked by iceberg keels. Tabular iceberg drafts in excess of 330 m have been measured, and modeling studies suggest that nontabular iceberg drafts of 500 m are possible. We conclude that a modern ice-keel turbate deposit in the form of a poorly stratified diamicton is probably widespread on that part (54%) of the Antarctic shelf less than 500 m deep.
Keywords: Sørishavet; Weddellhavet; geofysikk; geologi; isberg; issfjell; oseanografi

Notes on Southern Ocean hydrography, sea-ice and bottom water formation - Foldvik, Arne; Gammelsrød, Tor (Palaeogeography, Palaeoclimatology, Palaeoecology, 1988)
The Southern Ocean circulation and sea-ice distribution is briefly described. The formation of extremely cold bottom water in the Weddell Sea and its relation to the floating Ronne-Filchner Ice Shelves is discussed. It is shown that a concentrated swift eroding bottom current with anomalous low ratio transports the cold and dense ice Shelf Water from the shelf towards large depths. Comments are made on possible implications of this process for the large-scale deep-water circulation and for the interpretation of sediment cores.
Keywords: Sørishavet; Weddellhavet; geofysikk; havis; havstrømmer; hydrografi; isshelf; oseanografi

Palaeoceanography of the subantarctic South Atlantic - Ciesielski, Paul; Kristoffersen, Yngve (Nature, 1987)
Keywords: Sørishavet; oseanografi

Photoadaptation in Antarctic phytopfankton: variations in growth rate, chemical composition and P versus I curves - Sakshaug, Egil; Holm-Hansen, Osmund (Journal of Plankton Research, 1986)
The response of phytoplankton to variations in the light regime was studied during the VULCAN and ACDA cruises in the Antarctic. Unenriched batch cultures of 12–19 days' duration reached chl concentrations of 10–50 μg−1 and exhibited exponential growth rates, with the maximal rate being 0.41 doubl, day−1. Ice edge algae exhibited maximum growth rates at photon flux densities (PFD) of 30–100 μE m−2S−1 and the growth rate was reduced by about 30% at 500–1000 μE m−2S−1 The chl/C ratio ranged between 0.004 and 0.018, with the lowest ratios at PFDs above 500 μE m−2S−1 chl/C ratios were also below maximum at PFDs below 40–50 μE m−2S−1 The C:N:P ratios were close to the Redfield ratios; the Si/C ratio averaged 0.16 (atoms), and the ATP/C ratio averaged from 0.0024 to 0.0050 in different culture senes. When thawed after having been frozen for 10 days, shade-adapted cultures were in a much better condition than sun-adapted ones. P versus I data showed that the maximum assimilation number varied from 0.75 to 4.4 μg C (μg chl)−1h−1. It varied inversely with the chl/C ratio; therefore the maximum carbon turnover rate varied little between samples (0.024/0.035 h−1). Low biomass communities exhibited relatively high values for α (the initial slope of P versus I curves), low values for 1sat (160–330 μE m−2S−1), and they were susceptible to photoinhibition. In contrast, communities dominated by Odontella weissflogii exhibited low values for α, a high value for Isat (560 μE m−2S−1 and they tolerated high PFDs. The photo-adaptational status of the phytoplankton in natural water samples is discussed relative to the profile of water column stability and mixing processes.
Keywords: Sørishavet; alger; biokjemi; fytoplankton; marin biologi; oseanografi; planteplankton

Aleksandr Stepanovich Kuchin: the Russian who went south with Amundsen - Barr, William (Polar Record, 1985)
Aleksandr Stepanovich Kuchin (1888–1912) was already an experienced mariner and oceanographer when Amundsen invited him to join the Fram expedition of 1910–12. Expecting a voyage through the Barents Sea, Kuchin found himself on an expedition to the Antarctic. While Amundsen's sledging parties sought the South Pole, Kuchin remained with the ship, completing an excellent oceanographic survey of the southern Atlantic Ocean. Returning to Russia in 1912 he was recruited, by the geologist and explorer V. A. Rusinov to join a scientific expedition to Svalbard. As deputy leader of the party and captain of Gerkules, the expedition ship, Kuchin played an important role in the Svalbard survey. Then once again found himself heading in an unexpected direction: on completing the Svalbard work, Rusanov decided to attempt the Northern Sea Route to the Bering Strait. Gerkules disappeared and was never seen again; her loss, presumably in the Kara Sea, brought to an untimely end the career of a promising young polar explorer.
Publisher: Cambridge University Press
Keywords: Roald Amundsen; Sydpolsekspedisjonen; Sørishavet; biografier; oseanografi; polarområdene

Hydrographic observations on the southern Weddell Sea shelf break - Foldvik, Arne; Gammelsrød, Tor (Report of the Norwegian Antarctic research expedition (NARE) 1984/85, 1985)
Keywords: NARE 1984/85; Sørishavet; Weddellhavet; hydrografi; oseanografi

Oceanographic conditions on the Weddell Sea Shelf during the German Antarctic Expedition 1979/80 - Foldvik, Arne; Gammelsrød, Tor; Slotsvik, Noralf; Tørresen, Tor (Polar Research, 1985)
Keywords: Sørishavet; Weddellhavet; ekspedisjoner; hydrografi; isshelf; oseanografi

Circulation and Water Masses on the Southern Weddell Sea Shelf - Foldvik, Arne; Gammelsrød, Tor; Tørresen, Tor (Oceanology of the Antarctic Continental Shelf, 1985)
Keywords: Sørishavet; Weddellhavet; forskning; havstrømmer; oseanografi

Physical oceanography studies in the Weddell Sea during the Norwegian Antarctic Research Expedition 1978/79 - Foldvik, Arne; Gammelsrød, Tor; Tørresen, Tor (Polar Research, 1985)
Keywords: Sørishavet; Weddellhavet; havstrømmer; hydrografi; isshelf; oseanografi

The antarctic diatoms Thalassiosira dichotomica (Kozlova) comb. nov. and T. ambigua kozlova - Fryxell, Greta A.; Hasle, Grethe Rytter (Polar Biology, 1983)
Two small antarctic diatoms, usually missed by traditional collection methods, have been studied in light and electron microscopes. Porosira dichotomica has been transferred to Thalassiosira since its valve structure and process pattern agree better with that genus. T. dichotomica is unusual in that some lines of areola walls are extended, sail-like, out from the valve, supporting Kozlova's original drawings. T. ambigua, the smaller of the two, has many similarities in structure with T. dichotomica, but has granules on the margin, lacks the sail-like structures on the valve, and has minor differences in processes and areola size. Bands stay together in T. ambigua and show more fine structure than many species in the genus.
Keywords: Sørishavet; diatomeer; marin biologi; oseanografi

The response of Antarctic icebergs to ocean waves - Wadhams, Peter; Kristensen, Monica; Orheim, Olav (Journal of Geophysical Research: Oceans, 1983)
The heave, tilt, and strain responses of three Antarctic tabular icebergs to ocean waves were measured during a 1980–1981 cruise of HMS Endurance to the South Atlantic. The three icebergs, located near the South Sandwich and South Orkney islands, were instrumented with accelerometers, tiltmeters, and wire strainmeters, while a Waverider buoy was used to record the ocean wave field. The thickness of the icebergs was surveyed by a helicopter-borne radio echo sounder. The heave response occurred mainly at the swell period but with outbreaks of bobbing which lasted for a few cycles at a resonant period (about 40 s), which agreed well with the predictions of a numerical finite element model. The roll response occurred mainly at a long resonant period (40–50 s), which again agreed well with the model, but there was also a significant response at ocean wave periods (5–20 s), which exceeded predictions. The strain response had a component at very long periods, which is unexplained by theory, while the surface strain at ocean wave periods agreed with the simple analytical model of Goodman et al. (1980). Using this model it is possible to predict a wave height and period that will cause breakup of the icebergs, and we conclude that swell-induced breakup is likely to occur during major storms in the open southern ocean.
Keywords: Sør-Orknøyene; Sørishavet; brehylle; geofysikk; glasiologi; havbølger; isberg; isbreer; isbrem; isfjell; isshelf; oseanografi

Analysis of wave measurements at Bouvetøya - Arntsen, Øivind A; Snuggerud, John (Bouvetøya, South Atlantic Ocean : results from the Norwegian Antarctic Research Expeditions 1976/77 and 1978/79, 1981)
Keywords: Bouvetøya; ekspedisjoner; forskning; oseanografi

Hydrographic surveying around Bouvetøya - Fjørtoft, Jon H (Bouvetøya, South Atlantic Ocean : results from the Norwegian Antarctic Research Expeditions 1976/77 and 1978/79, 1981)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; hydrografi; oseanografi

Measurements of ocean current and bottom pressure near Bouvetøya, January–March 1979 - Foldvik, Arne; Gammelsrød, Tor; Tørresen, Tor (Bouvetøya, South Atlantic Ocean : results from the Norwegian Antarctic Research Expeditions 1976/77 and 1978/79, 1981)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; havstrømmer; oseanografi

Hydrographic and current measurements in the southern Weddell Sea 1979/80 - Gammelsrød, Tor; Slotsvik, Noralf (Polarforschung, 1981)
During the 1979-1980 expediton with the icebreaker Polarsirkel we had an excellent opportunity to study the physical oceanography of the inner part of the Weddell Sea. The ship followed the ice shelf barrier from Cape Norwegia at about 15 °W, and due to favourable ice conditions, it was able to penetrate all the way to the Antarctic Peninsula (60 0W). In this preliminary report we give a review of the physical oceanography programme which mostly consists of hydrographic (CTD) stations near the barrier, and also sorne current and water level measurernents. The different water masses observed are described and the possibility for a tidal-drlvcn upwelling near the ice shelf barrier is indicated.
Keywords: AABW; Sørishavet; Weddellhavet; bunnvannet; havis; hydrografi; isshelf; oseanografi; sjøis; sjøvann; vannmasser

Flow Around Icebergs - Foldvik, Arne; Gammelsrød, Tor; Gjessing, Yngvar (Annals of Glaciology, 1980)
Publisher: Cambridge University Press
Keywords: NARE 1978/79; Sørishavet; Weddellhavet; glasiologi; isberg; observasjoner; oseanografi; sjøvann

Some satellite tracked iceberg drifts in the Antarctic - Vinje, Torgny E (Annals of Glaciology, 1980)
Publisher: Cambridge University Press
Keywords: Sørishavet; drivis; havis; isberg; isdrift; isfjell; oseanografi; sjøis; vannmasser

The genus Thalassiosira: species with internal extensions of the strutted processes - Fryxell, Greta A; Hasle, Grethe Rytter (Phycologia, 1979)
Publisher: Taylor & Francis
Keywords: Sørishavet; diatomeer; marinbiologi; oseanografi

Melting of ice in sea water: a primitive model with application to the Antarctic ice shelf and ice bergs - Gade, Herman G. (Universitetet i Bergen, 1978)
Keywords: Sørishavet; havis; oseanografi

Weather and tide observations at Bouvetøya - Vinje, Torgny E (Results from Norwegian Antarctic Research 1974-1977, 1978)
Keywords: Bouvetøya; ekspedisjoner; forskning; meteorologi; observasjoner; oseanografi

Norwegian Antarctic Research. Past and Present. - Orheim, Olav (University of Chile, 1977)
Pages: 154-160 Publication Title: El desarrollo de la Antártica Place: Punta Arenas, Chile
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; NARE ekspedisjoner; Weddellhavet; geologi; glasiologi; havis; hvalfangst; kongress; marin biologi; marin geofysikk; marin geologi; meteorologi; oseanografi; symposium

Preliminary report of the 1976-1977 Norwegian Antarctic Research Expedition - Orheim, Olav (Norsk Polarinstitutt. Årbok 1976, 1977)
Keywords: Dronning Maud Land; M/V Polarsirkel; NARE 1976/77; Weddellhavet; marin geofysikk; oseanografi

Conditional instability of sea water at the freezing point - Foldvik, Arne; Kvinge, Thor (Deep Sea Research and Oceanographic Abstracts, 1974)
Keywords: AABW; Sørishavet; bunnvannet; havis; oseanografi; sjøis; sjøvann

Retrieval of current meters and study of thermohaline convection in the Weddell Sea - Bø, Redair; Foldvik, Arne; Kvinge, Thor (Antarctic Journal of the United States, 1973)
Keywords: Sørishavet; Weddellhavet; geofysikk; oseanografi

Sperm whales of the southeast pacific. Part III : Norphometry - Clarke, Robert; Paliza, Obla (Universitetsforlaget, 1972)
Publication Title: Hvalrådets skrifter : scientific results of marine biological research
Keywords: Sørishavet; forskning; hvaler; marin biologi; oseanografi

Morphologic Variability in Fasciculated Diatoms as Exemplified by Thalassiosira Tumida (Janisch) Hasle, Comb. Nov - Hasle, Grethe Rytter; Heimdal, Berit R; Fryxell, Greta A (Biology of the Antarctic Seas IV, 1971)
Keywords: Sørishavet; Weddellhavet; alger; marinbiologi; oseanografi; plankton

Diatoms: Cleaning and Mounting for Light and Electron Microscopy - Hasle, Grethe R; Fryxell, Greta A (Transactions of the American Microscopical Society, 1970)
Publisher: [American Microscopical Society, Wiley]
Keywords: Sørishavet; Weddellhavet; diatomeer; marinbiologi; oseanografi

The distribution of zooplankton in the southern ocean and its dependence on the circulation of water - Voronina, N. M. (Sarsia, 1968)
The distribution of zooplankton in the Southern Ocean depends on seasonal changes in quantity and on redistribution of the plankton by currents. In the upper 100 m the meridianal component of the current shifts the maxima of some species northwards from the divergence zone at a mean velocity of about 20 cm/sec. In the Antarctic convergence zone the water sinks at a mean velocity of 10.5 m/day. This brings about an increase of the total plankton amounting to about 3% per day. As the southward flow of deep water is very slow the transfer of plankton in this layer is negligible.
Publisher: Taylor & Francis
Keywords: Sørishavet; marin biologi; oseanografi; plankton

Sperm whales of the Southeast Pacific. Part I: Introduction. Part II: Size range, external characters and teeth - Clarke, Robert; Anelio, Aguayo L; Obla, Paliza (Universitetsforlaget, 1968)
Publication Title: Hvalrådets skrifter : scientific results of marine biological research
Keywords: Sørishavet; forskning; hvaler; marin biologi; oseanografi

On the tides at Norway Station and adjacent coastal areas of Antarctica - Hisdal, Vidar (Norsk Polarinstitutt, 1965)
Keywords: Den norske antarktisekspedisjonen 1956-60; Dronning Maud Land; ekspedisjoner; forskning; isshelf; observasjoner; oseanografi; tidevann

Pacific Antarctic waters - Midttun, Lars; Natvig, Johan (Hvalfangstmuseet, 1957)
Publication Title: Publikasjon fra Kommandør Chr. Christensens hvalfangstmuseum i Sandefjord. Scientific results of the Brategg Expedition, 1947-48
Keywords: Brategg ekspedisjon; Sørishavet; havbunnen; hydrografi; oseanografi; vannmasser

Tidal currents off the antarctic ice barrier, Queen Maud Land - Sverdrup, Harald Ulrik (Archiv für Meteorologie, Geophysik und Bioklimatologie, Serie A, 1954)
Observations of tidal currents in lat. 71° 01′ S, long. 10° 55′ W indicate that a semi-diurnal tidal wave progresses towards the WSW, that is, parallel to the main direction of the barrier. ForM2 the cotidal hour appears to be about 7h, in good agreement with the value 6.7h, that is derived from observations of the atmospheric pressure. Furthermore, the current measurements indicate that the ratio(K1+O1)/(M2+S2) is large, perhaps as large as 2.5.
Keywords: Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; Sørishavet; havstrømmer; klimaendringer; meteorologi; oseanografi; tidevann

On Conditions for the Vernal Blooming of Phytoplankton - Sverdrup, Harald Ulrik (ICES Journal of Marine Science, 1953)
Keywords: Sørishavet; forskning; oseanografi; planteplankton

The oceans : their physics, chemistry, and general biology - Sverdrup, Harald Ulrik; Johnson, Martin W.; Fleming, Richard H. (Prentice-Hall, 1942)
Keywords: Sørishavet; marin biologi; oseanografi

Consul Lars Christensen's Antarctic Cruise, 1933–34 (Polar Record, 1935)
Publisher: Cambridge University Press
Keywords: Antarktis; Thorshavn ekspedisjon; hydrografi; meteorologi; oseanografi

Fra »Norvegia« - Ekspedisjonene. Noen meteorologiske og oceanografiske resultater - Mosby, Hakon (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1935)
Publisher: Routledge
Keywords: Norvegia ekspedisjoner; Sørishavet; meteorologi; oseanografi; strømmer; vannmasser

Consul Lars Christensen's Antarctic Cruise, 1933–34 (Polar Record, 1934)
Publisher: Cambridge University Press
Keywords: Antarktis; Thorshavn ekspedisjon; hydrografi; meteorologi; oseanografi

Norvegia rundt sydpollandet : Norvegia-ekspedisjonen 1930-1931 - Isachsen, Gunnar (Gyldendal, 1934)
Publication Title: Publikasjon fra Kommandør Chr. Christensens hvalfangstmuseum i Sandefjord
Keywords: Antarktis; Hjalmar Riiser; Lars Christensen; Larsen; Norvegia ekspedisjonen; Sydpolen; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; meteorologi; oppdagelsesreiser; oseanografi

The waters of the Atlantic Antarctic Ocean - Mosby, Håkon (Scientific results of the Norwegian Antarctic expeditions 1927-1928 et sqq. Instituted and financed by consul Lars Christensen : Volume I, 1934)
Keywords: Antarktis; Bouvetøya; Norvegia ekspedisjoner; Sørishavet; hydrografi; oseanografi; strømmer; vannmasser

Wie entsteht die Antarktische Konvergenz? - Sverdrup, Harald Ulrik (Annalen der Hydrographie und Maritimische Meteorologie, 1934)
Keywords: Sørishavet; forskning; havstrømmer; meteorologi; oseanografi

Norwegian Explorations in the Antarctic, 1930-1931 - Isachsen, Gunnar (Geographical Review, 1932)
Publisher: [American Geographical Society, Wiley]
Keywords: Antarktis; Hjalmar Riiser; Lars Christensen; Larsen; Norvegia ekspedisjoner; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; meteorologi; oppdagelsesreiser; oseanografi

On the biology of southern Euphausiidae - Ruud, Johan Tidemand (Dybwad, 1932)
Publication Title: Hvalrådets skrifter : scientific results of marine biological research
Keywords: S.S.Vikingen 1929-30; Sørishavet; Weddellhavet; ekspedisjoner; hvalfangst; krill; marin biologi; oseanografi; plankton; zooplankton

I. Norske undersøkelser ved Sydpollandet 1929-1931. II. Norvegia-ekspedisjonen 1930-1931 : omseilingen av Sydpollandet - Isachsen, Gunnar (1931)
Publication Title: Meddelelser
Keywords: Antarktis; Hjalmar Riiser; Lars Christensen; Larsen; Norvegia ekspedisjonen; Sydpolen; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; meteorologi; oppdagelsesreiser; oseanografi

Nitrates and Phosphates in the Southern Seas - Ruud, Johan T (ICES Journal of Marine Science, 1930)
Keywords: S.S.Vikingen 1929-30; Sørishavet; Weddellhavet; ekspedisjoner; hval; hvalfangst; krill; marin biologi; oseanografi; plankton; zooplankton